Unsuspected Tracheal Web with Asthma-Like Symptom in a Young Female: Case Report - Moinazad-Tehrani, M; Agin, Kh (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Although most patients with asthma are easily controlled with appropriate medication, a small proportion of patients (approximately 5% of asthmatics) are difficult to control despite maximal inhaled therapy. Case Report: A 20-year-old girl admitted to the emergency ward (EW) of loghman hakim hospital in tehran with severe dyspnea. She was born with asphyxia for which oxygen therapy prescribed for two days. Conclusion: Congenital abnormality of the trachea can rarely present as asthma symptoms in adulthood. It is important to know, when encounter too difficult to treat asthma as the condition can be curable surgically.